An Analysis of Famous Person Semantic Memory in Aging. Issue 1 (1st January 2019) - Pistono, Aurélie; Busigny, Thomas; Jucla, Mélanie; Cabirol, Amélie; Dinnat, Anne-Lucie; Pariente, Jérémie; Barbeau, Emmanuel J
ABSTRACT: Background : In contrast to most memory systems that decline with age, semantic memory tends to remain relatively stable across the life span. However, what exactly is stable remains unclear. Is it the quantity of information available or the organization of semantic memory, i.e., the connections between semantic items? Even less is known about semantic memory for celebrities, a subsystem of semantic memory. In the present study, we studied the organization of person-specific semantic memory and its stability in aging. Methods : We designed a word association task based on a previous study, which consisted in providing the first word that came to the mind of the participants (15 participants for each age group 20–30, 40–50 and 60–70 years old) for 144 celebrities. We developed a new taxonomy of associated responses as the responses associated with celebrities name could in principle be very varied. Results : We found that most responses (>90%) could be grouped into five categories (subjective; superordinate general; superordinate specific; imagery and activities). The elderly group did not differ from the other two groups in term of errors or reaction time suggesting they performed the task well. However, they also provided associations that were less precise and less based on imagery. In contrast, the middle-age group provided the most precise associations. Conclusion : These results support the idea of a durable person-specific semantic memory in aging but show changes in the type of associations that elders provide. Future work should aim at studying patients with early semantic impairment, as they could be different from the healthy elders on such semantic association task.